MACAM - MACAM HADITS DARI SEGI KUALITASNYA - sarbanun sarbanun sarbanun (Ath Thariq Jurnal Dakwah dan Komunikasi, 2018)
Muslims must learn to overcome that the hadith of the Prophet (peace be upon him) as a guide to life after the Qur'an. Human laws that are not determined by law, how to practice them, are not specified in the Al-Qur'an verse in an absolute way and clearly, this makes the believers aware of the need to find a solution in this matter through al-hadith. A pious hadith is a hadith which is based on the Prophet Mhammad SAW whose sanad is in a group, narrated on fair and dhabit narrators until the end of the sanad, there are no irregularities and no flaws and no defects. The hasan hadith is a hadith that is justified by a just person, but his mind is less strong, not defective and odd. The dhaif hadith is a hadith in which there are no saheeh and hadots hasan conditions.